Particle–Fluid Suspension of a Non-Newtonian Fluid Through a Curved Passage: An Application of Urinary Tract Infections - Riaz, Arshad; Sadiq, Muhammad Adil (Frontiers in Physics, 2020)
The current investigation deals with the inclusion of solid particles in the flow of a non-Newtonian incompressible fluid passing through a symmetric, curved channel admitting flexible walls and exhibiting wavy characteristics for the passage of fluid. This analysis reflects the disease of white particles occurring in the flow of urine. The problem formulation is structured under the constraints of lubrication approach. The flow is considered to be laminar and steady by transforming the unsteady coordinates into wave frame coordinates. The governing equations have been formulated with the help of similarity transformations. The solution of boundary value problems has been handled by perturbation procedure. The analytical solutions for fluid and particulate phase velocities, mean flow rates, and pressure gradient profile have been presented, while a numerical treatment has been carried out for pressure rise. Analyses of fluid velocity and particulate suspension velocity, pressure gradient, and pressure rise curves under the variations of material parameters have been discussed by graphs. It is observed from this investigation that solid particles are curtailing the velocity and pressure of the liquid. It is also procured that the curvature of the channel also reduces the movement of the fluid and that the particulate suspension is occurring at the bottom of the container. It is very considerable that the increase in peristaltic pumping causes a decrease in the solid particle concentration. This theoretical analysis can help in curing the diseases like urinary tract infections (UTIs). The analysis may also be pertinent to the flow of other physiological liquids and industrial solicitation where peristaltic pumping is concerned.